2010
DOI: 10.1007/s10645-010-9152-3
|View full text |Cite
|
Sign up to set email alerts
|

Limits to Growth in Organic Sales

Abstract: SummaryThe price gap between organic and conventional food might explain the low market share of organics in the Netherlands. A real-life experiment was carried out in 2006 in order to determine the price sensitivity of consumer demand for organics. Consumer prices of selected organic products were reduced by up to 40% below current market levels. The price elasticity of demand was low, because not all consumers perceived the price reductions. Moreover, the offer of organic varieties is limited, as is the cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
9
1
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 6 publications
(4 reference statements)
6
9
1
2
Order By: Relevance
“…Their work showed a small impact of prices on demand because price elasticities are estimated with marginal price variations that are much lower than the price gap between organic and conventional products. Their results were in line with the work of Bunte et al (2010) who demonstrated that consumer demand for organic products in Netherlands does not changes when the price gap between organic and conventional products is deliberately reduced. These authors show that the reduction of organic price for some products, like organic milk, potatoes and rice do not shift demand much.…”
Section: Valuation Of Pesticide Reductionsupporting
confidence: 88%
“…Their work showed a small impact of prices on demand because price elasticities are estimated with marginal price variations that are much lower than the price gap between organic and conventional products. Their results were in line with the work of Bunte et al (2010) who demonstrated that consumer demand for organic products in Netherlands does not changes when the price gap between organic and conventional products is deliberately reduced. These authors show that the reduction of organic price for some products, like organic milk, potatoes and rice do not shift demand much.…”
Section: Valuation Of Pesticide Reductionsupporting
confidence: 88%
“…Although Bezawada and Pauwels () state that all organic consumer groups are somewhat price sensitive, they find that these consumers are nevertheless different, in that they react more to “enduring” actions, such as changes in assortment or regular price levels, but less so to promotional activities. An in‐store pricing experiment from 2006 in the Netherlands reveals that “consumer demand for organic food is sensitive to price changes when the price gap is high” (Bunte et al , 10).…”
Section: Results and Conclusion Per Research Questionmentioning
confidence: 99%
“…A London-area study found own-price elasticities for organic fruit and vegetables were approximately three times higher than for conventional ones (Fourmouzi et al 2012; also see Kasteridis and Yen 2012 for similar US results from 2006). An estimate of Dutch consumers' price elasticity of demand for several vegetables found the expected negative signs but never found elastic demand (Bunte et al 2010). Using data from a large retail chain in the northeastern US, Bezawada and Pauwels (2013) also found that organic products have greater own-price elasticity than conventional products.…”
Section: Previous Price Elasticity Estimatesmentioning
confidence: 98%